Targeting Immunomodulatory Agents to the Gut-Associated Lymphoid Tissue - Zgair, Atheer (Neuro-Immuno-Gastroenterology, 2016)
In addition to fluid haemostasis and lipid absorption, the lymphatic system and lymphoid tissues serve as the major host of immune cells where immune responses are evoked. Impaired function of the immune system might lead to serious diseases which are often treated by immunomodulators. This chapter briefly explores the physiology of an important part of the lymphatic system, the gut-associated lymphoid tissues (GALT). Currently used strategies for targeting GALT by immunomodulators for enhanced activity and/or decreased side effects are discussed. Strategies range from simple oral co-administration of immunomodulators with lipids to more advanced lipid-based formulations, polymer-based nanoparticle formulations and prodrugs. These targeting approaches successfully increase the concentration of immunomodulators achieved in the GALT and, more importantly, enhance immunomodulatory effects. Therefore, targeting immunomodulators to GALT represent a promising approach in the treatment of diseases where the immune system is actively involved.